2014
DOI: 10.1021/ac403026c
|View full text |Cite
|
Sign up to set email alerts
|

Equipment-Free Quantitative Measurement for Microfluidic Paper-Based Analytical Devices Fabricated Using the Principles of Movable-Type Printing

Abstract: Microfluidic paper-based analytical devices (μPADs) are a growing class of low-cost chemo/biosensing technologies designed for point-of-use applications. In this article, we describe MTWP (movable-type wax printing), a facile method for the fabrication of μPADs. MTWP is inspired by the Chinese movable-type printing and requires only a hot plate and homemade small iron movable components. It is able to pattern various wax microstructures in paper via a simple adjustment of the number, patterning forms or types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 66 publications
1
77
0
2
Order By: Relevance
“…A variety of techniques, including colorimetry [120][121][122][123], fluorescent [29,[123][124][125][126][127], luminescent [128], chemiluminiscent [128,129], photo-electro-chemiluminiscent, electrochemical [130,131], electro-chemiluminiscent [132,133], and photo-electrochemical [134] detections have been reported for paper and/or fiber-based bio-diagnostic platforms [2][3][4]135,136]. In the case of fluorescence readout, an important question is: "To what extent does the whiteness of the paper play a role in producing a background signal or perhaps participating in the bleaching effect?".…”
Section: Readout Outcomesmentioning
confidence: 99%
“…A variety of techniques, including colorimetry [120][121][122][123], fluorescent [29,[123][124][125][126][127], luminescent [128], chemiluminiscent [128,129], photo-electro-chemiluminiscent, electrochemical [130,131], electro-chemiluminiscent [132,133], and photo-electrochemical [134] detections have been reported for paper and/or fiber-based bio-diagnostic platforms [2][3][4]135,136]. In the case of fluorescence readout, an important question is: "To what extent does the whiteness of the paper play a role in producing a background signal or perhaps participating in the bleaching effect?".…”
Section: Readout Outcomesmentioning
confidence: 99%
“…These techniques include time-based, [9][10][11][12] distancebased, [13][14][15][16] and titration-based detection. [17][18][19] Philips and coworkers demonstrated time-based detection using an enzymatic reaction wherein a color change took place at different times depending on the concentration of the analyte.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Zhang and coworkers employed both the time and the number of the detection zones that changed color. 11,12,20 We also reported that titrimetric PADs where the endpoint is judged using only the naked eye to count the number of detection zones. 15,17 The method of counting the number of detection spots was also applied to a quantitative immunoassay.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in resource-limited areas where laboratory facilities are not accessible, wax offers an alternative technology for fabricating smart platforms for point-of-use devices. For instance, Songjaroen et al [20] produced a colorimetric PAD to detect glucose and BSA by simply wax dipping chromatographic paper, while Zhang et al [21] used heated patterned iron components, coated by wax, to stamp a wax pattern into chromatographic paper, detecting hydrogen peroxide. Among several chromatographic papers, Whatman #1 is often chosen as substrate in realizing these newgeneration diagnostic devices due to its surface area, cellulose purity, porosity, uniform thickness, and lightness [5].…”
Section: Introductionmentioning
confidence: 99%